Upaya Pengawas Madrasah Dalam Meningkatkan Kemampuan Guru Menggunakan Fasilitas Voice Note Whatsapp Sebagai Media Pembelajaran Jarak Jauh: Melalui Kegiatan Pendampingan Di MA Kedurang Bengkulu Selatan Tahun 2020 - Marusdi, Marusdi (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2022)
The research problem is the low ability of teachers to use the Whatsapp Voice Note facility as a distance learning medium. The research subjects were 12 teachers. Data collection techniques using observation and documentation techniques. Data validation with triangulation technique. Data analysis was carried out by comparing the results in the initial conditions, the results of the first cycle, the results of the second cycle. The results of the initial condition study showed that the teacher's ability was an average value of 44.00 (LESS). In the implementation of the first cycle the results of the assessment showed the number 66.83 (enough). In the implementation of the second cycle the results of the assessment showed an average value of 86.33 (GOOD). Looking at the data obtained from research results in research activities, it can be concluded that the assistance carried out by Madrasah Supervisors to 12 teachers at MA Kedurang, Kedurang District, South Bengkulu Regency was declared successful in increasing the ability of teachers to use the Whatsapp Voice Note facility as a distance learning medium.